Features of the mechanism of administrative and legal regulation of the civil aviation - Хом’яченко, Світлана Іванівна; Єряшов, Євген Кузьмович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
The article is devoted to research of features of mechanism of administrative and law regulations of civil aviation activity. The vision of author on this type of the branch regulations is also given through the norms of the Air Code of Ukraine.